Understanding children - Schickedanz, Judith A.; Hansen, Karen; Forsyth, Peggy D. (London Mountain View, CA Toronto : Mayfield Publ. Co., 1990)
Includes bibliogr. references and index.
Keywords: Child development; Child psychology; Adolescence